Kajian Konsep Multiple Intelligences Terhadap Penerapan Pembelajaran Di Madrasah Ibtidaiyah - Sjahidul Haq Chotib (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2018)
Theories about the types of intelligence possessed by humans. This theory is used as a learning method which is one of the alternative methods to dilute the deadlock in the learning process in both the formal and informal sectors. Multiple Intelligences come from two syllables, multiple and intelligence. In language, ordinary multiple is interpreted double, plural and diverse. Intelligence means intelligence or intelligence. Intelligences, in terminology - referring to the Large Dictionary of Indonesian Language - means perfect development of his mind, clever and sharp mind. Besides being smart, it can also mean perfect body growth, such as being healthy and strong physically. Based on the above definition it can be concluded that the most important indicator of intelligence is the perfection of mind, mind and physical growth. But the bitter reality in the practical and theoretical realm, intelligence is more often identified with mathematical, logical and language abilities. While moral and physical perfection seems not included in the realm of intelligence. In Islam - referring to the hadith hasan history of Abu Daud, Ahmad and Ibn Majah - intelligence is more oriented towards perfecting emotionality and spirituality. Al-kayyis man dana nafsah wa amila five ba'da al-maut (intelligent person is one who subdues his desires and prepares (life) after his death). The understanding of Multiple Intelligences operationally is a theory that says that there are eight types of intelligence (maybe even more but not yet identified). The eight types of intelligence are (1) language intelligence, (2) mathematical and logical intelligence, (3) spatial intelligence, (4) musical intelligence, (5) kinesthetic intelligence, (6) interpersonal intelligence, (7) intrapersonal intelligence, and (8) naturalist intelligence. The presence of the Multiple Intelligences theory in addition to perfecting the definition of intelligence also develops and enriches learning methods.